Evaluation of nutrient solutions for hydroponic culture "Strawberry" Fragaria x ananassa - Jara, Enoc (1999)
To determine the optimum nutritive solutions for strawberry, Fragaria x ananassa, Duchesne cv. Chandler under a system that uses fine gravel was evaluated two nutritive solutions formulas during vegetative period and three during the fructification period of de plant from December 1996 to August 1997. Destructive samplings were done at 60, 90, 160 and 220 days after treatment to evaluate the growth of the plant, absortion ot nutrients and the reducing sugar content in the fruit. No significant differences were tound between treatments in the vegetative period but there were in the reproductive's for the plant's height, flower and fruit number and percent of reducing sugar of the fruit and its weight. Neither there were significative differences in N, P, K, Ca, Mg and Fe percentages. Combinations of 200:40:300 ppm of NRK in the reproductive period give the best plant yield.